The Relative Performance of NDIR-based Sensors in the Near Real-time Analysis of CO2 in Air - Ki-Hyun Kim; Sudhir Kumar Pandey (Sensors, 2007)
In this study, the reliability of NDIR-based sensors was explored by evaluatingthe comparability between measurement systems in the near real-time analysis of CO2. Forthis purpose, replicate analyses were performed using sensors of two different model types(H-550 and B-530, ELT Company, Korea). Three replicate data of each sensor typecollected continuously by side-by-side analysis in three second intervals (a duration of 304hour) were evaluated for the relative performance of NDIR sensors. The reproducibility ofsensors, when assessed by relative standard error (RSE %) values of all sensor units,showed moderate changes with time with the overall mean of 2.33%. When CO2measurements from all NDIR sensor units were evaluated by correlation analysis, theresults showed strong comparability, regardless of the model type. The overall results ofthis study suggest that NDIR sensors are reliable enough to produce highly comparabledata at least in a relative sense.